Komposisi Amelioran Terhadap Pertumbuhan Dan Hasil Tanaman Kentang G1 (Solanum Tuberosum L.) Varietas Medians - Linlin Parlinah; Hudaya Mulyana; Lia Amalia; Nunung Sondari (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
This study aims to study the influence of the use of doses and composition of amelioran on the growth and yield of the potato varieties medians (Solanum tuberusum L.). The experiment was carried out in the Greenhouse Faculty of Agriculture University Winaya Mukti Tanjungsari Sumedang with a height of 850 m above sea level and the land order Andisols. The study was conducted in August to October 2017. The draft used is the group random draft, consisting of nine treatments and each repeated three times. Treatment of composition of Amelioran test is: A: control; B: Cow manure 10 ton ha-1; C: Cow manure 20 ton ha-1; D: Cow Manure 8 tons ha-1 + dolomite 1 ton ha-1 + biochar 1 ton ha-1; E: Cow manure 16 ton ha-1 + dolomite 2 ton ha-1 + biochar 2 ton ha-1; F: Cow Manure 8 tons ha-1 + dolomite 2 ton ha-1; G: Cow Manure 16 tons ha+ + dolomite 4 ton ha-1; H: Cow Manure 8 tons ha+ + biochar 2 ton ha-1; I: Cow manure 16 ton ha-1 + biochar 4 ton ha-1. The results of the experiment showed that the combined dose and composition of amelioran were not real to the growth, the results of potato plants except on tuber diameter. Administration of Ameliorant with a composition of cow manure 16 tons Ha-1 + dolomite 4 ton Ha-1 able to increase the diameter of potato tuber of 58% compared with control treatment.